Balloon coronary angioplasty and parenteral antiplatelet therapy for intraoperative myocardial infarction during general surgery: an attempt to balance benefits and risks – A case report - Nešković, Vojislava C.; Obradović, Slobodan D.; Popadić, Ana V.; Nikolić, Nenad B.; Stamenković, Dušica; Kostić, Zoran R. (Vojnosanitetski pregled, 2021)
Introduction. Cardiovascular complications remain one of the major risk factors for perioperative morbidity and bad outcome in non-cardiac surgery patients. Here we report a case of the patient suffering intraoperative ST-segment elevation acute myocardial infarction (STEMI) promptly treated with percutaneous balloon angioplasty and intravenous antiplatelet agents. Case report. A 62-year-old man, without previous history of cardiovascular morbidity, developed STEMI during abdominal surgery. Due to profound hypotension with mean arterial pressure of less than 40 mmHg, surgery was promptly ended and patient transferred to intensive care unit. Within one hour after the end of the surgery, coronary angiography and successful balloon angioplasty of occluded right coronary artery were performed. Tirofiban infusion was started in recommended dose. Developed hemodynamic instability was related to hypovolemia and excessive drainage, reaching 1,500 mL of blood in the following 15 hours. The following morning, drainage persisted (additional 600 mL of blood) which resulted in profound hypotension (65/40 mmHg). Overall, the patient received 1,970 mL of blood, 6 doses of thrombocytes and 840 mL of fresh frozen plasma. All together, the patient had a favorable outcome, despite the occurrence of bleeding complications and hemodynamic instability. Conclusion. The choice of treatment strategy for patients suffering perioperative STEMI during major non-cardiac surgery is challenging. After major non-cardiac surgery, characterized by both high bleeding risk and high risk of stent thrombosis, balloon angioplasty instead of stenting along with parenteral antiplatelet treatment may be a fair therapeutic choice. Clinical choices have to be made individually, according to the weighted risks and benefits.
Keywords: perioperative period; digestive system surgical procedures; myocardial infarction; angioplasty, baloon; tirofiban